Energy Consumption Behaviors of 802.11 and S-MAC: Implementation on NS2.35 - Malik, Meena; Sharma, Mukesh (International Journal of Engineering and Technology, 2018)
The Sensor technology has made encouraging trends in the field of wireless Networks by its innovative methods and adaptability. The  fundamental issue for wireless sensor networks (WSN) is to minimize energy consumption at each node due to restricted energy source.   The sensor nodes generally get random deployment and  need cooperation to accomplish specific operation in the network like  monitoring or  tracking any target in the environment. Due to limited power source nodes need careful use of energy resources. This work targets on simulating the power consumption behavior and analyzing the performance of 802.11 and S-MAC protocol for medium access control layer in wireless networks. S-MAC improves energy consumption by allocating bandwidth in efficient manner and  avoiding causes of energy waste. After simulation, it was found that S-MAC is Power-Efficient over 802.11 without losing on the performance using NS-2.35. The paper mainly emphasize on representing the plot for energy matrices along with throughput, delay and packet delivery ratio.